Ensaios sobre preços dos produtos agrícolas no Brasil - Barbosa, Gerrio dos Santos (2017)
This dissertation consists of three chapters. However, the results obtained with the same data source, in order to analyze a convergence of wholesale prices of vegetables without distribution market. They use 37 horticultural products for 16 markets, covering the period from January 2007 to July 2015, with series of 103 observations. The first chapter comprises a linear approach, a unit root assay test for the balance sheet data and the estimation and the convergence, adopted in the studies of Dobado and Marrero (2005); Dreger et al. (2007); Wolszczak-Derlacz (2008) and Lindenblatt and Feuerstein (2015). The results indicate the validity of the Law of One Price for convergence in all products, since convergence violates this hypothesis for 33 products. (2008) and adapted to the Brazilian horticultural sector by Tabosa, Ferreira and Castelar (2008) and adaptation to the Brazilian horticultural sector by Tabosa, Ferreira and Castelar (2014), which tested a convergence of wholesale price markets. Therefore, the process of determining the Law of One Price (LPU), it is said that the convergence of prices occurs in the various markets analyzed, implying that prices converge to a certain steady state, ie a long-term equilibrium price. The tests do not reject the hypothesis that the model was estimated linear (Evans-Karras model). The results point to markets that are not subject to time limits, however, conditioned to transaction costs. In the last chapter, a database provided by Agrolink, which presented price quotations for the states of Mato Grosso, Brazil, Paraná and Rio Grande do Sul, with no period from March 2004 to November 2016, for a total of 152 Observations. Using a methodology developed by Vahid and Engle (1993), using the Beveridge-Nelson-Stock-Watson multivariate decomposition approach (BNSW). The decomposition test the presence of common long-term and short-term dynamics, with the Vector Autoregressive (VAR) estimation. The results indicate only a common trend for soybean-producing states, which suggests a convergence of long-term product prices. In the short term, the two cycles common among the states, which insinuate the difference in the crops of the markets. Mato Grosso stands out as a reference state, there is a strong positive correlation with the common cycle 1, while Paraná and Rio Grande do Sul have a negative correlation with this cycle, suggesting that there is a capital transition to the state of Mato Grosso.